Agent for the treatment of wastewater, method of preparation thereof and method of treatment of wastewater. - Mohamed Din, Mohamed Shariff; Md Yusoff, Fatimah; Banerjee, Sanjoy; Khatoon , Helena (2010)

(untitled)
The present invention relates to an agent for the treatment of wastewater containing immobilized periphytic microalgae in alginate beads, to a method of preparation of said agent as well as to a method of treatment of wastewater using the immobilized periphytic microalgae in alginate beads for rapid and efficient removal of toxic compounds from wastewater. The beads can be used effectively in the treatment of wastewater containing high amounts of toxic compounds such as ammonia, nitrite and soluble reactive phosphorous compounds.